2008
DOI: 10.4261/1305-3825.dir.1710-08.1
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal schwannoma of the middle turbinate: imaging findings

Abstract: 129S chwannomas are lesions that arise from the neural sheath of peripheral nerves, autonomic nerves, or cranial nerves. Nerve sheath tumors of the head and neck region mainly involve the eighth cranial nerve with only 4% occurring in the paranasal sinuses (1, 2). Occasionally, malignant schwannomas also occur in the paranasal sinuses. Sinonasal schwannomas do not have specific radiologic findings. The tumor rarely extends intracranially or intraorbitally, and imaging features can be similar to malign neoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Neurilemmomas are predominantly benign, and the English literature only contains isolated cases of malignant schwannomas [5,6]. Tumor incidence in the sinonasal tract is not related to sex or age, with cases occurring in children and the elderly[4,7-15]. In our present study, all five cases occurred in the nasal cavity, with two in the nasal vestibule and three in the nasal septum.…”
Section: Discussionmentioning
confidence: 51%
“…Neurilemmomas are predominantly benign, and the English literature only contains isolated cases of malignant schwannomas [5,6]. Tumor incidence in the sinonasal tract is not related to sex or age, with cases occurring in children and the elderly[4,7-15]. In our present study, all five cases occurred in the nasal cavity, with two in the nasal vestibule and three in the nasal septum.…”
Section: Discussionmentioning
confidence: 51%
“…Even in extensive diseases, no recurrence was reported after endoscopic surgery. 36,47,62 In our review, endoscopic surgery was done in most cases (52.1%). Some small anterior tumors were excised with a safe margin without endoscopy.…”
Section: Discussionmentioning
confidence: 93%
“…The search yielded 52 studies and a total of 71 patients, including this reported case. 1,2,7,9 -11,13 -58…”
Section: Discussionmentioning
confidence: 99%
“…Schwannoma sinonasal bisa berasal dari sinus atau septum. 5,7 Namun, pada kasus ini asal tumor tidak bisa ditentukan karena massa tumor Sinus Maksila melekat pada sinus dan septum.…”
Section: Diskusiunclassified